A study on the selection, training and tournament strategies of the 22-peat Tainan City men's table tennis team at the National Games (1984-2011) - Chen, M.-K.; Chin, P.-C.; Chou, T.-Z. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The fact of that Tainan men table tennis team hit 22-peat for the National Games from 1984 to 2011 has made the remarkable records of table tennis competition in National Games. My study aims to study Tainan men table tennis team training process and key factors to reach 22-peat. The research methods took mainly historical research and partly interview to collect data. To follow were the results which were based on the collection of data. First, it didn`t go smoothly to win the games every year. There were five time peat was almost discontinued due to high competitive tournament. Fortunately, they won the games by their actual strength. The financial support came from City Hall, Central Table Tennis Committee, and Cooperative Bank. Second, Tainan men table tennis team was established in 1977 by coach Mr. Chung-Hsiung Lin. There were 43 players in total to participate and won 22-peat games in 27 years. Many players were selected to become national players and passed down their strength of good convergence to next generation. Third, the coach trained players individualized. He planned the whole training programs not only in skills and physical training, but also in psychological counseling. While era and ideas have changed for the past thirty years, the methods of management have also changed from the militarization to democratization. Fourth, four points were the key factors to win 22-peat: (1) An unimpeded channel to university attracts good players to come to be trained. (2) Discipline and obedience were emphasized in strict team training and management. (3) Good team understanding and high cohesion. (4) Good experience inheritance made no lack of talent.